Analysis of independent agriculture program for Empowered Village Women (Permata) from CSR PT Pertamina EP Adera Field - Masona, Sarion; Ulfah, Nurhayatul; Nasution, Adam S.; Rosadi, Hengky; Sari, Dewi Ratna; Ripandi, Irfan (Indonesian Journal of Multidisciplinary Science, 2024)
The purpose of the program is to improve the economy, health and environmental management of the community based on village women's empowerment through the cultivation of Family Medicinal Plants (TOGA) and Organic Vegetables with the smart agriculture method to increase the efficiency and productivity of plants by optimizing the use of water, fertilizer and energy resources. The program intervention from CSR PT Pertamina EP Adera Field in the form of the Independent Agriculture Program for Empowered Village Women (PERMATA) has the goal of improving the economic, health, and community environmental management. The specific objectives of this program are four things: First, the formation of a model garden as a community learning center location for the practice of cultivating organic toga and vegetables with smart agriculture methods. The data collection technique is carried out by observation with active participation, in-depth interviews, documentation and focus group discussion. The results of the Community Satisfaction Index (IKM) assessment show that the people of Pengabuan Village, Abab District, Penukal Abab Lematang Ilir Regency, South Sumatra Province are satisfied with the program that has been carried out. Increasing the role of women to play an active role in fulfilling the socio-economic needs of families and communities, as well as reducing community stigma against leprosy patients in the village through support efforts from groups in harmony with nature through supporting herbal drinks.